Identification of host proteins interacting with Toxoplasma gondii GRA15 (TgGRA15) by yeast two-hybrid system - Liu, Qing; Li, Fa-Cai; Elsheikha, Hany M.; Sun, Miao-Miao; Zhu, Xing-Quan (BioMed Central, 2017)
Background